Locomotor Activity as the Leading Factor of Psychophysical Preparation of Young Students - Natalia Panhelova (Jan Długosz University in Częstochowa, 2019)
The article presents data on the current state of health, physical preparedness, motor activity of students in non-sports profile higher education establishments. It was found that low levels of physical condition of students is determined by a number of factors, among which, the lack of their motor activity, as well as non-rational approaches of the governing bodies and the administration of some higher educational establishments to organizing teaching and extracurricular physical training of future specialists are the major ones. It contains data relative to the main functions of motor activity. The basic provisions of the letter of the Ministry of Education and Science of Ukraine of 09.25.2015 №1 / 9-454 "Regarding the organization of physical education in higher education".